Dynamics of solitons to the ill-posed Boussinesq equation - Tchier, Fairouz; Aliyu, Aliyu Isa; Yusuf, Abdullahi; İnç, Mustafa (Springer Heidelberg, 2017)
In this paper, we analyze the dynamic behavior of the ill-posed Boussinesq equation (IPBE) that arises in nonlinear lattices and also in shallow water waves. Some solitary wave solutions are obtained by using the solitary wave ansatz method and the Bernoulli sub-Ode. By applying the technique of nonlinear self-adjoint, a quasi self-adjoint substitution for the IPBE is constructed. The classical symmetries of the equation are constructed. Then, we used along with the obtained nonlinear self-adjoint substitution to construct a set of new conservation laws (Cls).
Keywords: Traveling-Wave Solutions; Conservation-Laws; Backlund Transformation; Evolution-Equations; Systems